Effects of livestock grazing on plant species diversity vary along a climatic gradient in northeastern Iran. Issue 4 (7th August 2020) - Rahmanian, Soroor; Hejda, Martin; Ejtehadi, Hamid; Farzam, Mohammad; Pyšek, Petr; Memariani, Farshid
Abstract: Questions: (a) Do patterns of species diversity and composition differ between plots exposed to high vs. low grazing intensity? (b) Do these differences vary among three regions with different climates, representing a gradient from arid to sub‐humid conditions? Location: Northeastern Iran. Methods: We compared plots intensively grazed by sheep and goat (HG) to plots with low grazing intensity (LG), across three climatic regions: arid, semi‐arid and sub‐humid. Species diversity (expressed as Shannon H ) was compared using linear mixed‐effect models. Dissimilarity analysis was used to estimate the compositional heterogeneity of different types of plots, reflecting the differences in species composition. Indicator Species Analysis was used to identify individual species associated with particular types of plots. Results: The HG plots had lower values of Shannon H than LG plots, across all climatic regions. Further, the effect of grazing on species diversity varied between the climatic regions, with the most pronounced differences between the HG and LG plots in the sub‐humid region. Although no differences in species diversity were detected between the three climatic regions, compositional heterogeneity was the highest in the sub‐humid region and the lowest in the semi‐arid region, with the most pronounced differences between the HG and LG plots in the sub‐humid region. Indicator Species Analysis showed significant main effects of both climate and grazing on species composition, revealing species that respond to grazing in each of the three climatic regions. Conclusions: Overgrazing was detected to reduce the diversity of species in all three climatic regions, even though its effect was most pronounced in the sub‐humid region. Therefore, the control of overgrazing or reduction of its intensity appears an effective management tool for protecting species diversity, applicable in areas with different climates. Abstract : The effects of overgrazing were investigated in three climatic regions in northeastern Iran: arid, semi‐arid and sub‐humid region. Overgrazing was detected to reduce diversity and affect species composition in all three regions. However, its effects were most profound in the sub‐humid region, as these species may be adapted to competition rather than to the stress and disturbance induced by overgrazing.